Ternary Fe-Cu-TiO2 xerogels for the degradation of dye acid yellow 36 - S. López-Ayala; E.C. Menchaca; M.A. Méndez-Rojas; J. Uruchurtu; Z.A. Uribe-Rosales; M.E. Rincón (Desalination and Water Treatment)
Wastewater containing recalcitrant and toxic dyes such as acid yellow 36 (AY36) can be discolorated by using heterodoped semiconductors. The effectivity of ternary Fe-Cu-TiO2 xerogels on the degradation of AY36 under laboratory lighting (visible light) conditions is reported. AY36 is a recalcitrant and toxic azo dye that can cause tumor formation, gut disorders, and induce neurotoxicity/hepatotoxicity. Due to its recalcitrance, its safe elimination is difficult. Composites of Fe-Cu-TiO2 obtained by sol-gel synthesis form a tandem and doped semiconductor system with improved performance for dye degradation. Doping promotes the presence of interband states that enhance the electronic conductivity and response to visible light. For Cu-doping, the CuO phase is also present and proved relevant for increasing the reaction rate, most likely for the rectifying effect that avoids charge carrier’s recombination. The nanomaterials were used to degrade the AY36 dye under darkness, under visible, and UV light irradiation conditions. The doped-semiconductor heterojunction/H2O2 system generates Fenton-type reactions, with HO• radicals generation, accompanied by oxygen evolution, which improves the degradation efficiency. First-order reaction rate constants of k = 0.1, 0.18, 0.19 min‐1 under darkness, visible, and UV light conditions were obtained. TOC tests indicated a 67.4 and 70.9 % degradation under visible and UV light, respectively. Total discoloration (100 %) and a significate decrease in TOC were achieved due to the characteristics of these nanomaterials.